Design cloud computing to monitor and controller for high voltage networks 400 KV - Hamed Khudair Khalil; Laith Ali Abdul Rahaim; Shamam Fadhil Alwash (Cognitive Robotics)
A high-voltage network (400 kV) is a system that has multiple control and communication elements and acts as a link between generating stations and transmission lines; it is considered one of the smart networks. The advantage of a smart grid over a traditional utility grid is that it uses a two-way communication mechanism. The monitoring and control system for this network utilizes SCADA and RTU, but it comes at a high cost. Nonetheless, it is preferable to have a system that is economical, intelligent, and dependable. In this research, we will design a remote monitoring and control system for high-voltage networks using cloud computing technology with IoT applications that support the above-mentioned systems and can be developed in case of any expansion in electrical networks. We use this system to remotely monitor smart network equipment and control the closing and opening of breakers using protection relays and sensors. This proposed system uses the ESP 32 microcontroller to send warning signals to remote operators via the Internet, utilizing the MQTT protocol. This system utilizes the Thing Board platform in conjunction with Quick Set (5030) software, enabling control via a laptop and smartphone.